Talk Show Program Production Strategies on Campus Radio as an Information Medium for University Students - M. Rifkia Andika (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
The rapid development of information and communication technology has transformed media consumption patterns among university students. The emergence of digital media and Artificial Intelligence (AI)-based technologies has contributed to a decline in students' interest in campus radio, highlighting the need for more innovative program production strategies to maintain its role as an information medium. This study aims to analyze the production strategies of talk show programs at the campus radio station of the Yasni Bungo Institute of Islamic Studies (IAI Yasni Bungo) as a source of information for university students. The study employed a qualitative approach using a case study design. Data were collected through observations, in-depth interviews, and documentation. The participants included campus radio managers, broadcasters, and university students selected through purposive sampling. Data were analyzed using the stages of data reduction, data display, and conclusion drawing, while the trustworthiness of the findings was ensured through source, technique, and time triangulation. The findings indicate that the production strategy for talk show programs has been implemented through three main stages: planning, implementation, and evaluation. During the planning stage, the radio management designed programs tailored to students' needs and gradually promoted them through social media using creative approaches aligned with current digital trends. Nevertheless, students' interest in campus radio remains relatively low, as most prefer obtaining information through digital media and AI-based applications, which are perceived as faster, more practical, and more accessible. These conditions present significant challenges for the IAI Yasni Bungo Campus Radio in improving program quality, strengthening digital promotion, and developing broadcasting innovations through the integration of podcasts, social media, and streaming services. The study concludes that the success of talk show program production strategies depends not only on the quality of broadcast content but also on the ability of radio managers to understand changing audience behavior and effectively utilize digital technology to support the production process, thereby ensuring that campus radio remains relevant as an information medium within higher education institutions.